2020
DOI: 10.1080/21622671.2020.1743204
|View full text |Cite
|
Sign up to set email alerts
|

Labouring under a delusion? Scotland’s national questions and the crisis of the Scottish Labour Party

Abstract: In recent years, the Scottish Labour Party has lost its once dominant position in Scottish politics. Its support has collapsed and it now faces multiple political challenges, relating both to cleavages in Scottish politics over the constitution and Brexit, and to divisions within the party over its leadership and direction. Employing semi-structured elite interviews with key figures within the party hierarchy and focus groups with grassroots activists, this article examines the causes of this crisis through an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…No references to the UK constitutional arrangements were made. of nationalist sentiments, allowing the party to sidestep pressing constitutional debates (Bennett et al, 2020;Brown Swan, 2022). But in resolving one problemsecuring a more stable alignment with the UK party-Scottish Labour now encountered another, as internal opposition to the party's subordinate status to London again became a divisive issue.…”
Section: Uk Labour Under Corbynmentioning
confidence: 99%
See 3 more Smart Citations
“…No references to the UK constitutional arrangements were made. of nationalist sentiments, allowing the party to sidestep pressing constitutional debates (Bennett et al, 2020;Brown Swan, 2022). But in resolving one problemsecuring a more stable alignment with the UK party-Scottish Labour now encountered another, as internal opposition to the party's subordinate status to London again became a divisive issue.…”
Section: Uk Labour Under Corbynmentioning
confidence: 99%
“…Denied much political room for manoeuvre by debates over a second referendum, senior figures in Scottish Labour fell back on the radical-sounding, but largely undefined, idea of putting the UK on an entirely new, 'federal' footing. According to Bennett et al (2020), those emphasising a federalist platform were overwhelmingly grassroots activists and trade union officials, whereas politicians and advisors were less keen. In Westminster, Baroness Bryan was charged with developing Labour's constitutional offering, but the completion and publication of a report on the subject was forestalled by the 2019 election, and Corbyn's resignation.…”
Section: Dilemmas Of Electoral Strategy and Political Leadershipmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the party has become a catch-all party in Wales, attracting support from a variety of different identities and interests. 30 This contrasts with the fortunes of Labour in Scotland, where the party has failed to articulate a 'Scottish' brand of Labour politics, 31 as well as in England, where, as Ailsa Henderson and Richard Wyn Jones argue, Keir Starmer needs to take identity seriously if he is to successfully respond to the growing force of Englishness. 32 Welsh Labour has shown that articulating progressive values in nation-bounded terms, as well as invoking traditions, myths and symbols that resonate with the public imagination, can help to construct this type of distinct identity.…”
Section: Emilymentioning
confidence: 99%